The Impact of Dental Anxiety on Oral Health-Related Quality of Life in Children: A Longitudinal Study in Jakarta, Indonesia - Ni Made Nova Indriyani; Dea Albertina; Desiree Montesinos; Rheina Weisch Fedre; Winata Putri (Crown: Journal of Dentistry and Health Research, 2023)
Introduction: Dental anxiety is a common problem among children, and it can have a significant impact on their oral health-related quality of life (OHRQoL). This longitudinal study aimed to investigate the impact of dental anxiety on OHRQoL in children in Jakarta, Indonesia. Methods: A cohort of 200 children aged 6-12 years was recruited from six elementary schools in Jakarta. Dental anxiety was assessed using the Children's Fear Survey Schedule-Dental Subscale (CFSS-DS) at baseline, 6 months, and 12 months. OHRQoL was measured using the Child Perceptions Questionnaire (CPQ11-14) at the same time points. Sociodemographic data and oral health status were also collected. Linear mixed models were used to assess the association between dental anxiety and OHRQoL over time, adjusting for potential confounders. Results: Dental anxiety was significantly associated with lower OHRQoL scores at all time points. Children with higher dental anxiety scores reported more problems with oral symptoms, functional limitations, emotional well-being, and social well-being. This association persisted even after adjusting for age, gender, socioeconomic status, and oral health status. Conclusion: Dental anxiety has a significant negative impact on OHRQoL in children. Early identification and management of dental anxiety are crucial to improve children's oral health and overall well-being.